Características del consumo de ciprofloxacino en pacientes hospitalizados en el Hospital Nacional Edgardo Rebagliati Martins - durante el año 2007 - Gutiérrez García, Karina Mabel (2008)
A descriptive, cross-sectional, retrospective study of the drugs use, whose overall objective was to determine the characteristics of the use of Ciprofloxacin in hospitalized patients in of the Edgardo Rebagliati Martins National Hospital (ERMNH), during the year 2007, which used the methodology the defined daily dose for one hundred beds/day (DDD/100beds-day). It was made with computerized information of use of Ciprofloxacin. The data were drawn from the database hospitalary management system. Use of Ciprofloxacin in hospitalized patients in ERMNH - year 2007 was higher among female with 60.47% and in the age group of 60-69 years with 16.79%, and the 29.69% of this use was as clinical criteria and 73.31% according to the microbiological criteria. The most common diagnostic for which indicates the use of Ciprofloxacin were postoperative wound infections (26.67%) and urinary tract infections (62.88%), for systemic and oral use Ciprofloxacin respectively. Use of Ciprofloxacin in ERMNH during the year 2007 was 12 DDD/100beds-day and shows a not significant tendency to increment during the period of study. The service of hospitalization ERMNH higher use of Ciprofloxacin was General Surgery-6B with 28 DDD/100 beds-day. The cost of total annual use of Ciprofloxacin in ERMNH during the year 2007 was 81318.72 new soles and the service of hospitalization that was generated higher cost of use of Ciprofloxacin was Internal Medicine-11C with a total cost of 5162.67 new soles